Noninhibitory binding of human interleukin-2-activated natural killer cells to the germ tube forms of Candida albicans. - Arancia, G (1995)
During incubation in vitro with yeast or germ tube forms of Candida albicans, only 2 to 6% of freshly isolated human natural killer (NK) cells (> 85% CD16+, CD56+, CD3-; < 15% CD3+; cytolytic for the NK-susceptible target K562 but not for the NK-resistant target DAUDI), were seen to interact with the fungal cells. As seen under the electron microscope, the contact area had a limited extent and was narrow, and neither the surface nor the intracytoplasmic organization of the NK cell was altered. In contrast, more than 30% of interleukin-2-activated NK (LAK) cells (> 96% CD16+, CD56+, CD3-; 1.5% CD3+; cytolytic for both K562 and DAUDI targets) interacted closely with the fungus. This interaction was particularly extensive with the surface of the fungal germ tube that was intimately enveloped by villous protrusions from the lymphocyte surface. The fungus-interacting LAK cell also showed a remarkable redistribution of surface microvilli and polarization of cytoplasmic organelles, such as the Golgi apparatus, centrioles, and granules, toward the area of fungal contact. Together with the elevated cytolytic potential against the K562 and DAUDI targets, all the morphological data suggested the presence of a potentially active lytic machinery in the fungus-interacting LAK cell. Nonetheless, two independent assays for anticandidal activity did not show consistent killing or fungal growth inhibition by either fresh NK or LAK cells. While offering direct evidence of the strong interaction between human LAK cells and the germ tubes, precursors of tissue-invasive hyphal forms of C. albicans, our observations also suggest that this interaction may not be sufficient to kill the fungus or arrest its growth.